The improved growth performance of Cyprinus carpio by dietary yeast culture depends on improvement of intestinal structure and digestive enzyme activities rather than changes of intestinal microbiota composition - Shengqiang Tao; Jiahao Wang; Zhiyuan Xue; Yichen Bai; Yi Wang; Wenhao Zhou; Tingyin Liang; Yuhong Yang (Aquaculture Reports)
The ban of antibiotic growth promoters can influence the total production of aquaculture. Yeast culture (YC) possesses the ability to enhance immunity and has been supplemented into diet to try to increase production. To investigate the effects of YC on the growth and its mechanisms, four diets supplemented with 0 g/kg (Y0), 10 g/kg (Y1), 20 g/kg (Y2), 30 g/kg (Y3) YC were assigned to Cyprinus carpio for 8 weeks (three replicates per diet, 30 fish in each replicate). The results showed that dietary 10 g/kg YC significantly increased weight gain rate (WGR), protein efficiency ratio (PER), specific growth rate (SGR) and reduced feed conversion ratio (FCR) (P < 0.05). Also, the apparent digestibility of lipids and proteins was significantly increased by dietary 10 g/kg YC compared with the Y0 group (P < 0.05). Meanwhile, fish fed 10 g/kg YC showed significantly higher intestinal villus height and width as well as the digestive enzyme activities of trypsin and lipase than Y0 group (P < 0.05). However, no significant differences was found in the composition of intestinal flora between the Y1 and Y0 groups (P > 0.05). Whereas, excessive levels of YC significantly reduced abundances of Fusobacteriota and increased that of Proteobacteria (P < 0.05). Simultaneously, the growth performance, apparent digestibility of dry matter and protein and intestinal trypsin activity in the Y3 group were also significantly lower than that of Y1 group (P < 0.05). In summary, our results supported the applicability of dietary 10 g/kg YC as a growth promoter for common carp through the improvement of intestinal digestive enzymes and intestinal structure but not gut microbial composition, and suggested that excessive levels of YC may cause imbalances in the gut flora, resulting in growth inhibition.